2018
DOI: 10.1111/bjdp.12234
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational associations of the approximate number system in toddlers and their parents

Abstract: From birth, humans are able to discriminate quantities using the approximate number system (ANS). However, previous methods have only been suitable to examine ANS functioning in infancy and older children. The goals of this study were twofold: first, to modify an existing method of assessing ANS functioning for toddlerhood; and second, to investigate individual differences in toddlers' ANS performance by examining correlations with their parents' ANS acuity. Using a preferential looking paradigm, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 65 publications
(119 reference statements)
0
14
2
Order By: Relevance
“… Piazza et al (2013) demonstrated that adult speakers of Mundurukú, a language that lacks number words beyond five and therefore severely limits the mathematical concepts that speakers can articulate, have less precise representations of approximate quantities than do individuals from Western cultures who speak languages that include number words. Similarly, evidence with Western adults suggests that formal math education is associated with greater precision of the ANS ( Nys et al, 2013 ; Lindskog et al, 2014 ). Furthermore, two recent studies utilized cross-lagged longitudinal designs have shown that children’s math skills predict later ANS acuity, even when controlling for earlier ANS acuity, suggesting that math may relate to changes in the ANS over time (authors, under review; Mussolin et al, 2014 ; but see He et al, 2016 ).…”
Section: Discussionmentioning
confidence: 95%
“… Piazza et al (2013) demonstrated that adult speakers of Mundurukú, a language that lacks number words beyond five and therefore severely limits the mathematical concepts that speakers can articulate, have less precise representations of approximate quantities than do individuals from Western cultures who speak languages that include number words. Similarly, evidence with Western adults suggests that formal math education is associated with greater precision of the ANS ( Nys et al, 2013 ; Lindskog et al, 2014 ). Furthermore, two recent studies utilized cross-lagged longitudinal designs have shown that children’s math skills predict later ANS acuity, even when controlling for earlier ANS acuity, suggesting that math may relate to changes in the ANS over time (authors, under review; Mussolin et al, 2014 ; but see He et al, 2016 ).…”
Section: Discussionmentioning
confidence: 95%
“…Parents' cognitive and mathematical basic (i.e., ANS) and more advanced (i.e., calculation) abilities (intergenerational transmission). Based on previous literature, we expected significant associations between children's early numeracy skills and their parents' ANS skills (see Navarro et al, 2018). Our analysis of the link with parents' calculation skills is more explorative, but we expected to see at least a weak association with children's early math.…”
Section: The Current Studymentioning
confidence: 91%
“…Recently, some studies addressed the issue of intergenerational transmission of literacy (van Bergen et al, 2015) and math (Braham and Libertus, 2017;Navarro et al, 2018;Bernabini et al, 2020) skills not only in children with dyscalculia but also in typical populations. Navarro et al (2018) found that parents' Approximate Number System (ANS) skills were related to toddlers' number processing and that this relation was independent of children's vocabulary or parents' perceived math ability, suggesting a specific intergenerational transmission of the ANS. In another study (Braham and Libertus, 2017), conducted on 54 children (5-9 years old) and their parents, children's ANS acuity positively correlated with their parents' ANS acuity.…”
Section: Intergenerational Paths Of Math Skillsmentioning
confidence: 99%
See 2 more Smart Citations